2017
DOI: 10.1016/j.jaci.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

An epigenome-wide association study of total serum IgE in Hispanic children

Abstract: Background Total immunoglobulin E (IgE) is a therapeutic target in allergic diseases. DNA methylation in white blood cells (WBCs) was associated with total IgE in an epigenome-wide association study (EWAS) of Caucasians. Whether DNA methylation of eosinophils explains those findings is insufficiently understood. Methods We tested for association between genome-wide DNA methylation in WBCs and total IgE in two studies of Hispanic children: the Puerto Rico Genetics of Asthma and Lifestyle Study (PR-GOAL, n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 34 publications
5
60
1
Order By: Relevance
“…In addition, our cell counts are estimated from the methylation data using a reference dataset instead of being directly sorted and counted in the original blood samples. Whereas the method has been previously validated [76] and previous EWAS analyses have found strong correlations between estimated and cell sorted measures [22], it may not perform well in predicting proportions of rarer cell types in the blood, such as eosinophils, as they may be subject to less favourable signalto-noise ratios than high abundance cell types. However, we attempted to counter the potentially poor estimation of cell counts by using surrogate variables in our EWAS analysis, a reference-free method of adjusting for unknown confounding factors.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, our cell counts are estimated from the methylation data using a reference dataset instead of being directly sorted and counted in the original blood samples. Whereas the method has been previously validated [76] and previous EWAS analyses have found strong correlations between estimated and cell sorted measures [22], it may not perform well in predicting proportions of rarer cell types in the blood, such as eosinophils, as they may be subject to less favourable signalto-noise ratios than high abundance cell types. However, we attempted to counter the potentially poor estimation of cell counts by using surrogate variables in our EWAS analysis, a reference-free method of adjusting for unknown confounding factors.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…A recent EWAS of IgE in Hispanic children [22] reported associations with DNA methylation in CpGs annotated to the ZFPM1 (cg04983687, cg08940169) and ACOT7 (cg09249800, cg21220721, cg11699125) genes. We observe similar strong associations with CpG sites annotated to the same genes in the unadjusted EWAS of current asthma at 7.5 years (Additional file 2: Tables E1 and E2).…”
Section: Comparisons With Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that, while it should not be surprising that cell subtype effects need to be taken into account in the interpretation of functional genomics studies, it is probably worth paying more attention to the characterization of the variability of cell subtypes as an insight into the phenotype being tested, rather than discarding the information as merely confounding 1,[45][46][47] . Phenotypes may indeed result from cellular reprogramming, but it is highly plausible that the polycreodism model of altered cell repertoires in a tissue is another potentially very powerful mechanism for mediation of phenotypic changes.…”
Section: Discussionmentioning
confidence: 97%
“…Associations of wheeze with DNA methylation may be expected to capture a wider variety of biological processes that underlie respiratory conditions. Previous studies have reported an association between peripheral blood DNA methylation and IgE (21,22) , an important mediator of atopic or inflammatory diseases such as asthma. However, whether these associations are also present for the asthma phenotype has not been assessed.…”
Section: Introductionmentioning
confidence: 99%